UPAYA MENINGKATKAN KEPUASAN KONSUMEN MELALUI KUALITAS PELAYANAN, CITRA MERK, DAN HARGA PADA UMKM SAMBAL PECEL MBAK TI DI KOTA KEDIRI - Febriana, Tesha Fransiska; Ernestivita, Gesty; Suhardi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Culinary industry had been growth is currently quite rapid, so various types of businesses must compete with each other to attract buyers. In addition, the ease of opening a culinary business is currently very open by only selling in a few strategic places according to them. One type of UMKM in Kediri City in the culinary industry is Sambel Pecel Mbak Ti, which produces packaged pecel sauce for consumption as well as souvenirs. There is rapid competition in the culinary industry, so every business must show excellence in the form of services provided to buyers, then image in the eyes of consumers, and prices that are able to compete. This study will discuss the effect of either partially or simultaneously the quality of service, brand image, and price on consumer satisfaction. This research is a quantitative type with the distribution of questionnaires to consumers totaling 40 people. Data were obtained through observation, questionnaires, and interviews with the parties concerned. The data were then analyzed in multiple regression, with correlation results stating that the variables of service quality, brand image, and price have a significant influence on customer satisfaction